Assessing the impact of menopause on salivary flow and xerostomia - Minicucci, E. M. [UNESP]; Pires, R. B C [UNESP]; Vieira, R. A. [UNESP]; Miot, Hélio Amante [UNESP]; Sposto, M. R. [UNESP] (Wiley, 2013)
Background: The aim of this study was to evaluate the symptoms of dry mouth and salivary flow in menarche and menopausal women. Methods: Objective and subjective assessment of salivary function were analysed by Xerostomia Inventory and Visual Analogue Scale questionnaire in menopausal and menarche women (control group). Salivary flow was evaluated by a chemical absorption stimulation test. Each subject provided three saliva samples: S1, non-stimulated saliva; S2, saliva initially stimulated with two drops of citric acid 2.5%; and S3, saliva super-stimulated with two drops of citric acid 2.5% every 30 seconds for two minutes. Results: No intergroup association was observed between Xerostomia Inventory and Visual Analogue Scale questionnaire. In both groups, the salivary flow was greatest at S3, followed by S2 and finally S1. Salivary flow was lower in the menopausal group compared to the control group only in S2 and S3. Conclusions: In the menopausal group, the salivary flow showed reduction but without clinical symptoms of dry mouth. It is important to normalize salivary flow to prevent oral abnormalities and maintain oral health. © 2013 Australian Dental Association.
Keywords: Hyposalivation; menarche; menopause; salivary flow; xerostomia